HUBUNGAN KONSELING ASI, DUKUNGAN SUAMI, DAN DUKUNGAN BIDAN DENGAN PERILAKU IBU UNTUK MEMBERIKAN ASI OLEH IBU POST PARTUM DI BPM NINA MARLINA, S.ST, SUKARAJA BOGOR TAHUN 2021 - Retno Nur Chabibah; Yusmiati Yusmiati; Agusanti Br. Ginting (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2023)
Based on the WHO report, in 2015 approximately 1.5 million children died due to poor feeding. Meanwhile, the number of babies who are exclusively breastfed is less than 15%. The fact found in the field is that some babies do not get breast milk due to various factors, based on a preliminary study, at BPM Nina Marlina, S. ST, Sukaraja Bogor, it is found that the number of mothers who provide exclusive breastfeeding is only (34%) of the number of visits by 322 babies during 2020 .The purpose of this study is, the Relationship of Breastfeeding Counseling, Husband Support, and Midwife Support by Mother Motivation to Give Exclusive Breastfeeding to Post Partum Patients at BPM Nina Marlina, S. ST, Sukaraja Bogor in 2021.The research design used by researchers in this study is to use descriptive analytical methods. by using a cross section design. The population in this study were all Post Partum mothers at BPM Nina Marlina, S. ST, Sukaraja Bogor in 2021 as many as 34 people with 34 samples. Technok sampling Total sampling. Analysis using Univariate with percentages. Bivariate with chi squere.It is known that the value (P = 0.001) is smaller than the value of α (0.05), so it can be concluded that there is a relationship between breastfeeding counseling and mother's motivation in giving exclusive breastfeeding. It is known that the P value (0.010) is smaller than the α value (0.05), so it can be concluded that there is a relationship between husband's support and mother's motivation in giving exclusive breastfeeding. It is known that the P value (0.000) is smaller than the α value (0.05), so it can be concluded that there is a relationship between support from midwives and mother's motivation in giving exclusive breastfeeding.